Recombinant human erythropoietin treatment in a rat model of nephrectomy - Ribeiro, Sandra (2016)
We aimed to evaluate the impact of rHuEPO on anemia, renal function and structure in chronic renal failure (CRF), using a rat model of nephrectomy. Male Wistar rats, 12 weeks old, were divided in 3 groups: CRF (induced by a two-stage 5/6 nephrectomy); rHuEPO-CRF (treated with 100 IU/kg/week during 3 weeks) and Sham (surgery without mass reduction). Hematological and biochemical studies were performed. Kidney tissue sections were stained with Periodic acid-Schiff for histological studies. Statistical analysis were performed using the Mann-Whitney test. At the end of protocol, CRF group presented anemia (p<0.05) and reduced glomerular filtration rate (GFR), whereas rHuEPO-CRF group showed an improvement in hematological parameters (p<0.05) and a slight improvement in GFR. The histopathological analysis of kidney tissue showed that CRF group presented global glomerulosclerosis, tubular necrosis, IFTA and arteriolosclerosis. Due to surgery, we also found some inflammatory cell infiltration. The rHuEPO-CRF group presented mesangial expansion and a reduction in tubulointerstitial and vascular lesions, as compared to CRF rats. The introduction of rHuEPO corrects the anemia associated with renal failure and improved the degree of renal lesions, slowing the progress of renal failure.